Organic nanomaterials synthesis, characterization, and device applications - Torres, Tomas; Bottari, Giovanni (Wiley, 2013)
"This book offers comprehensive and up-to-date coverage of functional organic nanomaterials. Chapters present the views of leading experts on how organic nanomaterials can be synthesized and prepared, analyzed and characterized, studied, organized at the nanoscale, and incorporated into devices for real-world applications. Due to the interdisciplinary nature of organic nanomaterials, the book appeals to those involved in chemistry, physics, materials science, polymer science, and (chemical and material) engineering. Topics include conducting hybrid materials, biomaterials, carbon nanotubes, photovoltaics, dye-sensitized solar cells (DSCs), lithographic techniques, bioassays, sensors, and nanomedicine"--